Modelling a Viennese ballroom: agent-based simulation to investigate complex behaviour. Issue 2 (3rd March 2020) - Bicher, M.; Winkler, S.; Körner, A.
ABSTRACT: Dancing Viennese Waltz in one of the great historic ballrooms is an important and indispensable part of Austrian culture. This dance, while being tradition, is quite difficult to perform, especially if the dance-floor is crowded. There, it is additionally challenging to avoid collisions with other dancers, as they pace through the ballroom at a high velocity. Dependent on the dancer's skill level, spinning speed can be adjusted to succeed. This paper presents an agent-based waltz model which makes it possible to investigate the influence of heterogeneously skilled dancers on the movement smoothness of the dancing crowd. Herein, each agent represents one dancing couple in reality and it moves on the dance-floor by a rotatory motion with periodically switching rotation axes. Interaction between agents occurs via inelastic collisions. By performing a couple of case studies, we analyse and quantify the widespread rumour that the presence of only a few unskilled dancers disturbs the flow of the dancing crowd.